IMPACT OF DIGITIZATION AND MOBILE BANKING ON THE BANKING SECTOR STRUCTURE IN POLAND - Kozak, Sylwester; Golnik, Bartosz (Management and Administration Journal, 2021)
The article presents the results of examining the changes that have occurred in connection with the digitization of banking in Poland and its impact on this segment. The data is taken from the National Bank of Poland, the Polish Financial Supervision Authority, and the Prnews.pl website. A descriptive, statistical and Pearson correlation method were used. The results indicate an increasing share of customers using banking products in a digital way. The number of both website and mobile applications customers is growing. Despite the general increase in the number of people using banks, the number of bank branches as well as the employees working them has decreased. Mobile applications may soon become the main sales and service channel for banking products, the number of customers of banks using them regularly increases. In fact, the rise in digitization for banking and the decrease in the number of branches and employees are strongly correlated. The increasing usage of online and mobile banking is influenced by convenience, availability, and a reduction in the time customers spend on purchasing and servicing their products. Banks are interested in developing these types of services in order to both meet the changing needs of customers and to save on operating costs.